2008
DOI: 10.1111/j.1365-2842.2007.01834.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forward head posture on condylar position

Abstract: There are several reports suggesting that forward head posture is associated with temporomandibular disorders and restraint of mandibular growth, possibly due to mandibular displacement posteriorly. However, there have been few reports in which the condylar position was examined in forward head posture. The purpose of this study was to test the hypothesis that the condyle moves posteriorly in the forward head posture. The condylar position and electromyography from the masseter, temporal and digastric muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 30 publications
1
43
0
15
Order By: Relevance
“…8 The forward head position moves the mandibular condyle from a normal position to a higher and more posterior region in the mandibular fossa than in normal head posture. 9 Moreover, painful stimuli in the cervical region may lead to pain in the facial region. 10,11 Some clinical studies have found that the use of diagnostic criteria for TMD associated with photographic and magnetic resonance imaging analyses do not confirm the correlation between TMD and head and cervical postures.…”
Section: Changesmentioning
confidence: 99%
“…8 The forward head position moves the mandibular condyle from a normal position to a higher and more posterior region in the mandibular fossa than in normal head posture. 9 Moreover, painful stimuli in the cervical region may lead to pain in the facial region. 10,11 Some clinical studies have found that the use of diagnostic criteria for TMD associated with photographic and magnetic resonance imaging analyses do not confirm the correlation between TMD and head and cervical postures.…”
Section: Changesmentioning
confidence: 99%
“…The hypothesis of an association between head posture and the limitation of mandibular growth could also be postulated 23 .…”
Section: -6 -Cranio-cervical Posturementioning
confidence: 99%
“…A mandible, and its condyles 23 , held in a retruded position could be an indicator of this possibility because it would mean the kinematics of the TMJ had been altered as well as the mechanism for muscular control for correcting the anticipated hyper-extension of the head.…”
Section: -6 -Cranio-cervical Posturementioning
confidence: 99%
See 1 more Smart Citation
“…Change in head posture affected swallowing 20) , the path of mandibular movement 3,5) , and activity of head-neck muscles 2,19) . Head posture is also associated with temporomandibular disorders 13) . Masticatory movement has been reported to be accompanied by head movement (pitching of the head) 1,[8][9][10]12) .…”
Section: Introductionmentioning
confidence: 99%